Adult Education (and Educators) and the Mental Health Crisis - Cheryl Zelle (Adult Education Research Conference, 2023)
The field of adult education needs to engage in deep reflection and discourse about adult educators’ role in responding to the mental health crisis in higher education.
Keywords: Adult educators; mental health; well-being; COVID pandemic; higher education